MENINGKATKAN HASIL BELAJAR IPS MATERI SUMBER DAYA ALAM MENGGUNAKAN MODEL PICTURE AND PICTURE PADA SISWA KELAS IV SD NEGERI 200107/10 PADANGSIDIMPUAN - Nasution, Aisyah; Zulfadli, Zulfadli; Nurbaiti, Nurbaiti; Ilahi, Afdhal; Sucahyo, Eko; Ningtyas, Rani Kusuma; Nurzanna, Nurzanna (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2024)
This study aims to determine the application and learning outcomes of students in  learning natural resources material using the Picture and Picture learning model in class IV SD Negeri 200107/10 Padangsidimpuan The type of assessment used is Classroom Action Research (PTK). The research subjects were fourth grade students at SD Negeri 200107/10 Padangsidimpuan. The instruments used were observation and tests in collecting data based on the results of this study. The results of applying the Picture and Picture model measured using the observation sheet had increased as can be seen in cycle I, 64% was obtained. Enough criteria with a score of 16 and in cycle II, it increased to 91%. Very good criteria with a score of 22. Student learning outcomes have increased as can be seen in cycle I obtained a percentage of 50% who completed with less criteria and 50% did not complete with less criteria, an increase in cycle II obtained a percentage of 78% who completed with Good criteria and 22% incomplete with Less criteria. The results of the assessment showed that students completed learning by 50% in cycle I and students completed learning by 78% in cycle II. The conclusion obtained is that there is an increase in social studies learning outcomes on natural resources using the Picture and Picture method for fourth grade students of SD 200107/10 Padangsidimpuan